Support grid integration of offshore wind power. Issue 1 (May 2021) - Han, Xingning; Zhao, Feifei; Ma, Jinlong; Ye, Xueshun; Sun, Yong
Abstract: China has a cumulative installed offshore wind capacity of 6.8 GW, making it the third largest in the world. Compared with Europe, which is the largest offshore wind power market, there are still gaps to substantially tapping the offshore wind potentials of China. This paper aims to investigate advanced experience of offshore wind power, and explore innovative approaches for offshore wind deployment and grid integration in China. Development and issues caused by offshore wind power in UK, Germany and Denmark have been investigated, including technological progress, curtailment, and network congestion and redispatch needs. The grid integration approaches to re-enforcement of network to accommodate offshore wind power are also analysed. Contrastive analysis is taken about stakeholders and planning process of offshore wind among UK, Germany, and Denmark. Construction suggestions are proposed for the development of offshore wind power in China during the 14 th Five Year Plan period.